Implementation of Online Learning in Improving Learning Motivation and Understanding of Grade 3 Students at Madrasah Ibtidaiyah: Implementasi Pembelajaran Daring dalam Meningkatkan Motivasi Belajar dan Pemahaman Siswa Kelas 3 di Madrasah Ibtidaiyah - Kristanti, Desita Rini; Nurdyansyah, Nurdyansyah (Psikologia : Jurnal Psikologi, 2023)
This study aims to find solutions to improve student learning outcomes, find out what difficulties are received by students during the online learning process and provide learning motivation to class 3 students at MI Nurul Huda. The formulation of the problem in this study are: analyzing the implementation of online learning in increasing the learning motivation of class 3 students at MI Nurul Huda and analyzing the implementation of online learning in improving the understanding of students in class 3 at MI Nurul Huda. The method used in this study is a qualitative method using data collection techniques by means of observation, interviews / interviews and documentation. The subjects of this study were: the principal, teachers and students of class 3 MI Nurul Huda Ngampelsari which has four classes, and each class is represented by one student. The results of this study indicate that online learning at MI Nurul Huda Ngampelsari has no problems and goes well, then research on student learning motivation is still enthusiastic and timely during online learning and for student understanding during online learning in general students still do not understand to interpret and extrapolate the lessons that have been given.